Heuristic Search Algorithm for the Single-row Machine Layout in an Automated Manufacturing System. (2016) - Murthy, P.B.G.S.N.; Ranganayakulu, Jinka; Vidhu, K.P.; Rao, K. Venkata
Abstract: Machine lay out is one of the important factors that affects material handling time, manufacturing time and cost. In this work, design of manufacturing facilities is made with the consideration of repeat operations at the same manufacturing facility, in sequence moments. There are six flow-line analysis methods reported in the literature. Among these six methods, two best methods are considered in this paper. They are Flow Line Analysis (FLA)-5 for bidirectional flow lines and Flow Line Analysis-6 for unidirectional flow lines. A random insertion perturbation scheme is used to find out neighborhood sequences from a seed sequence. The seed sequences are found from the FLA 5 and 6 methods. A hybrid search algorithm is proposed by combining FLA-5 and 6 with Simulated Annealing algorithm to find out optimum machine layout with less material handling time. Twenty five sets of data are created and tested with the proposed algorithm.